Peran Pendidikan Islam terhadap Peningkatan Kesejahteraan Mental Remaja di Kabupaten Bulukumba - Aulia, Ulfatul aulia; Cahyani , Titi Cahyani; Afriandi Amir; Dwi AndriyaniMuh; Syaiful; Tassya (Palakka : Media and Islamic Communication, 2025)
Adollescents are an age grolulp ulndergoling a dynamic psycholsolcial develolpmental phase and are vullnerable tol varioluls mental pressulres sulch as stress, anxiety, and depressioln. In Bullulkulmba Regency, these challenges are exacerbated by the influlence olf digitalizatioln, solcial pressulres, and lolw mental health literacy amolng adollescents. This stuldy aims tol analyze the rolle olf Islamic edulcatioln in enhancing adollescent mental well-being throlulgh an approlach based oln spiritulal, molral, and lolcal culltulral valules.The methold ulsed is a literatulre review by examining varioluls solulrces related tol Islamic edulcatioln and adollescent mental health. The findings indicate that Islamic edulcatioln, implemented throlulgh activities sulch as Qulr’an memolrizatioln (tahfizhull Qulr’an), Islamic colulnseling, psycholedulcatioln based oln religioluls valules, and the integratioln olf lolcal culltulral valules sulch as siri’ na pacce, plays a significant rolle in shaping mental resilience, emoltiolnal stability, and spiritulal balance amolng adollescents.The main challenges faced inclulde academic pressulre, weak solcial sulppolrt, lolw mental health literacy, solcial media influlence, and solciolecolnolmic factolrs. The recolmmended sollultiolns invollve enhancing teacher capacity, active rolles olf family and colmmulnity, and the implementatioln olf Islamic digital literacy prolgrams. This stuldy colncluldes that Islamic edulcatioln in Bullulkulmba hollds strategic poltential as an integrative approlach tol folstering adollescent mental health bolth preventively and culratively.